A Study The Fundamental Frequency of Voice and Natural Frequency of Vocal Tracts on an Indian Population of Different Age Ranges - SAMUEL, GEORGE (Journal of All India Institute of Speech and Hearing)
The study was concerned with the frequency response of the vocal tract. This was undertaken on the assumption that the vocal tract is an acoustical system having a series of coupled resonance elements, with resonance peaks in the response frequencies. It is believed that the frequencies of the peaks of the resonances approximate the natural response frequencies of th.e system. The attempt at locating these peaks was undertaken in this study for males and females in different age ranges, between 7 to 16 years and 20 to 25 years. The study was also concerned with finding the fundamental frequency for these groups. The fundamental frequency of the voice was considered as indicating pitch in the present study.